TRPV1-Mediated Microglial Autophagy Attenuates Alzheimer’s Disease-Associated Pathology and Cognitive Decline - Wang, Chenfei; Huang, Wei; Lu, Jia; Chen, Hongzhuan; Yu, Zhihua (Frontiers in Pharmacology, 2022)
Autophagy is a major regulator of the ageing process of the central nervous system and neurodegeneration. Autophagy dysfunction has been implicated in the pathogenesis of Alzheimer’s disease (AD). TRPV1 was reported to regulate autophagy to protect against foam cell formation and reduce the release of inflammatory factors in atherosclerosis. In this study, pharmacological activation of TRPV1 with the TRPV1 agonist capsaicin induced autophagy in a TRPV1-dependent manner in both primary microglia and BV2 cells. TRPV1-mediated autophagy regulated glycolysis and oxidative phosphorylation by controlling the expression of genes required for aerobic glycolysis and mitochondrial respiration in primary microglia. TRPV1 agonist capsaicin decreased amyloid and phosphorylated tau pathology and reversed memory deficits by promoting microglia activation, metabolism, and autophagy in 3xTg mice. These results indicate that TRPV1 was a potential therapeutic target for AD, which suggests that capsaicin should be further assessed as a possible treatment for AD.